India China : Rethinking Borders and Security - Ling, L. H. M. (Book collections on Project MUSE., 2016)
"Challenging the Westphalian view of international relations, which focuses on the sovereignty of states and the inevitable potential for conflict, the authors from the Borderlands Study Group reconceive borders as capillaries enabling the flow of material, cultural, and social benefits through local communities, nation-states, and entire regions. By emphasizing local agency and regional interdependencies, this metaphor reconfigures current narratives about the China India border and opens a new perspective on the long history of the Silk Roads, the modern BCIM Initiative, and dam construction along the Nu River in China and the Teesta River in India. Together, the authors show that positive interaction among people on both sides of a border generates larger, cross-border communities, which can pressure for cooperation and development. India China offers the hope that people divided by arbitrary geo-political boundaries can circumvent race, gender, class, religion, and other social barriers, to form more inclusive institutions and forms of governance"--